Self-Efficacy, Motivation, and Employee Performance in Hospitality Industry: A Mediation Analysis - Wardhana, Daniel Yudistya; Harsono, Harsono (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
It is hypothesized in several research that that times of crisis and turbulence can lead to considerable changes in how organizations, especially those in the inherently volatile tourism industry, manage their strategies. This research primarily aimed to investigate the relationship between self-efficacy and employee performance, with an emphasis on the intermediary role of motivation in a hospitality companies located in Yogyakarta, Indonesia. To fulfil this aim, a quantitative approach was adopted, involving a survey distributed to a group of 100 employees. The gathered data was then examined using Partial Least Square-Structural Equation Model (PLS_SEM) to determine the effect of each variable. The results of the study indicated that Self-Efficacy had significant influence on Motivation and Performance. Also, the results that the indirect path of self-efficacy, motivation and performance is significant and positive and classified as partial mediation. This research offers practical implications for the tourism industry particularly in terms of how effective the management of tourism companies, as business stakeholders maintain their employee’s performance effectively through real implementation particularly during periods of crisis.